The Relationship Between Knowledge and Attitude About Anemia with Compliance to Consume Iron Supplement Tablets in Female Adolescents of Grade X at State Senior High School 13 Surabaya - Ainur Wachidah Choirun Niza; Annas Buanasita; Mujayanto; Riezky Faisal Nugroho; Fahmi Hafid; Sharifah Intan Zainun Sharif Ishak (Journal of Nutrition Explorations, 2024)
The transition from childhood to adulthood that adolescents go through is known as the "adolescent stage". Anemia is a common nutritional condition among adolescent girls in Indonesia. This study aimed to determine the relationship between knowledge and attitudes of adolescent girls regarding anemia and their willingness to take Fe (iron) tablets. The type of research is analytic observational with a cross sectional approach. A total of 68 panelists were purposively selected. The results showed that most had a good understanding of anemia, but there were still many who did not take Fe (iron) tablets. Chi-Square test was applied to analyze the data and it was found that adolescent girls in class X SMA Negeri 13 Surabaya did not know anything about anemia and did not take blood enhancement tablets. In conclusion, most of the adolescent girls have positive attitude and knowledge related to anemia, but some adolescents do not consume Fe (iron) supplements. Suggestion: Inspire adolescent girls to consume Fe (iron) supplements along with providing comprehensive information related to anemia and motivation.